Distribution of nutrients across the edible components of a modelled typical Australian lamb: A case study. (24th January 2023) - Wingett, Kate; Alders, Robyn
Abstract : Abstract: Achieving sustainable development is one of the greatest challenges for humanity. This includes producing food in a way that enhances ecosystem, animal and human health, at the farm level and more broadly. To measure the enhancement brought about by animal production systems, producers, livestock industries and governments need a deeper understanding of the nutrient distribution across the edible parts of the animal. This case study examined the nutrient distribution across food products (carcase and co-products (edible offal and slaughter fat)) derived from a typical Australian lamb, using modelling with secondary data. Due to data gaps, some edible offal products were not able to be incorporated into the model (blood, trachea, omasum, abomasum, intestines, feet/tendons and head meat). Co-products accounted for approximately 24% of total edible product (i.e., carcase and co-product) by weight, 18% of the total protein and 37% of the total fat. With regards to micronutrients, the co-products contained 42% of the total iron content and the liver had more vitamin A, folate and vitamin B12 than the carcase and other co-products combined. This case study highlighted the nutritional value of co-products, especially liver, in the context of the whole animal and, the importance of including co-products in assessments of animal production systems.